2013
DOI: 10.4103/2278-330x.114134
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in plasma lipid profile in oral submucous fibrosis patients: A case control study

Abstract: Background:Lipids are major cell membrane components essential for various biological functions including cell growth and division of normal and malignant tissue. They are also required for maintenance of structural and functional integrity of all biological membranes. Alteration in the plasma lipid profile has been associated with a variety of cancers and precancerous conditions including those of the head and neck region.Aim:The present study aimed to evaluate the alteration in plasma lipid profile in oral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
2
6
0
Order By: Relevance
“…Similarly, Gupta and Gupta [13] observed a significant decrease in plasma total cholesterol, HDL, TC, and TGL in the patients with precancerous lesions and conditions, Singh et al [14], reported a significant decrease in TC, HDLC and TGL in the oral cancer group. Kumar et al [15] and Kanthem and Guttikonda [16] found significantly decreased lipid levels in OSMF patients, Neerupakam et al [17] noted a significant decrease in the total cholesterol and HDL in oral cancer subjects, which was similar to the results of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Gupta and Gupta [13] observed a significant decrease in plasma total cholesterol, HDL, TC, and TGL in the patients with precancerous lesions and conditions, Singh et al [14], reported a significant decrease in TC, HDLC and TGL in the oral cancer group. Kumar et al [15] and Kanthem and Guttikonda [16] found significantly decreased lipid levels in OSMF patients, Neerupakam et al [17] noted a significant decrease in the total cholesterol and HDL in oral cancer subjects, which was similar to the results of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Our study results coincided with the studies done by Kumar et al .,[ 15 ] in which they showed a significant decrease in TC, HDL and LDL in patients with OSMF as compared to the controls. Their study also showed no significant changes in the levels of TGs and VLDL.…”
Section: Discussionmentioning
confidence: 99%
“…18 Oral submucous fibrosis due to its malignant potential is a clinically significant disease. [9][10][11]22 As there is no definitive treatment for Oral sub-mucous fibrosis, thus focus should be placed on prevention, early diagnosis and evaluation of the malignant potential of the disease. Lipids are cell membrane components essential for various biological functions including growth and division of normal and malignant tissues they are also imperative for the structural and functional integrity of biological membranes.…”
Section: Discussionmentioning
confidence: 99%